Experimental and numerical analysis of three‐point bending tests of steel beams with web holes. Issue 2 (1st September 2021) - Matos, Rui; Craveiro, Hélder; Lopes, Tiago; Zanon, Riccardo; Tibolt, Mike
Abstract: Steel profiles are commonly used as filler‐beams for composite decks of road and railway bridges. The filler beams are encased in a concrete slab with reinforcement bars parallel and transversal to the steel profile. To ensure the passing of the transversal reinforcement rebars, the web of the filler‐beams must be previously drilled with a suitable diameter. The closely spaced steel beams and the reinforced concrete act compositely in the longitudinal direction. In current practice, steel profiles are cambered in the vertical plane to compensate the deflection of the steelwork under self‐weight of the deck, permanent loads and equivalent concrete shrinkage load. In this investigation a set of experimental tests was undertaken on simply supported beams aiming to reproduce the precambering procedure of steel profiles with web holes. In the structural tests, the main goal was to assess the overall performance of the steel element with holes on the web for transversal reinforcement, relating the different camber values with the applied load and observed ovalization of the web holes. Material mechanical characterization was also undertaken in this investigation. Based on the experimental results, finite element models were developed and calibrated, aiming to undertake extensive parametric studies to gather relevant data for the definition of a systematic procedure for precambering of steel beams with holes on the web for transversal reinforcement.